Abundance and distributional ecology of cetaceans in the central Philippines - Dolar , M. Louella L.; Perrin , William F.; Taylor , Barbara L.; Kooyman , Gerald L.; Alava , Moonyeen N. R. (J. Cetacean Res. Manage., 2023)
In general, little is known about cetacean abundance and distribution in Southeast Asia. This paper investigates the species composition, interactions/associations, abundance and distribution of cetaceans in an archipelagic tropical habitat characterised by deep, oceanic waters approaching the shore, high water temperatures and deep, stable thermoclines. Abundance is estimated using line transect methods. In addition, the cetacean fauna of the Sulu Sea is compared with those of other tropical marine ecosystems: the eastern tropical Pacific, the western Indian Ocean and the Gulf of Mexico. The most abundant species in the two study sites (eastern Sulu Sea and the Tañon Strait) was the spinner dolphin, Stenella longirostris; with a population estimate of 31,512 (CV=26.63%) in the eastern Sulu Sea and 3,489 (CV=26.47%) in the Tañon Strait. Other abundant species were the pantropical spotted dolphin (S. attenuata), Fraser’s dolphin (Lagenodelphis hosei) and the short-finned pilot whale (Globicephala macrorhynchus). Density and species-abundance rank varied between the two study sites, with generally higher densities in the Sulu Sea than in the Tañon Strait. An exception was the dwarf sperm whale, Kogia sima, whose density was 15 times higher in the Tañon Strait. Fraser’s dolphin ranked third in abundance in the Sulu Sea but was absent from the Tañon Strait. Environmental factors such as depth, site and temperature were observed to have a significant influence on the distributions of various species.